The Effect of Work Experience and Competence on Auditing with Auditor Performance as an Intervening Variable in Regional Inspectorate of Binjai City - Lubis, Munawwarah; Isa Indrawan, Muhammad (CV. Lafadz Jaya, 2023)
The purpose of this research is to analyze the effect of work experience and competency on auditing with auditor performance as an intervening variable. This type of research is associative quantitative. This research was conducted at the Regional Inspectorate Office of Binjai City. The population of this research is 79 employees, and the sample is a saturated sample. Data collection was carried out by distributing questionnaires. The data source for the research was primary data and the research model used was path analysis and the measuring tool used was Smart PLS version 3.3.3. The results of his research are Performance has a positive and significant effect on performance. Competence has no significant positive effect on Audit. Competence has a positive and significant effect on performance. Work Experience has no significant positive effect on Audit. Work experience has a positive and significant effect on performance. Competence influences Audit through Performance in a positive and significant way. Work Experience has a positive and significant effect on Audit through Performance.